Methods of breaking seed physical dormancy and germination in native species of Alhagi graecorum Boiss (Al-Agool ) - Sharashy , Omar (Journal of Pure & Applied Sciences, 2023)
Alhagi graecorum is a plant  belonging to the Fabaceae family and grows as wild perennial shrubby species. Seeds of this species possess seed physical dormancy and need to be removed to enhance germination, breaking of dormancy treatments were imposed on seeds to improve germination. Treatments include scarification with  sulfuric acid ( H2SO4 ) for 10, 20, 30 and40 minutes. The results showed highly significant difference between control and all the treatments of germination percentage ( GP ) was 96%, 96%, 97% and 97%, respectively, while recorded in control only 12%. As for the mean daily germination ( MDG ), the results revealed that, there was a significant differences between all  treated seeds and control, which was the fastest and most effective seeds germination on the third day of sowing were 84, 89, 90, 92 % respectively, while in control was 0 %. Mean germination time    (MGT)  decreased in all treated seed but statistically same while significantly different from the control. The minimum time was recorded  for 20 and 30 minutes was 3.14 and 3.14 days respectively.            We conclude from the results obtained that, the use of concentrated sulfuric acid 98%  achieved the highest GP and  MDG and the lowest MGT. This is the efficient method of breaking seeds dormancy and germination for native species of Alhagi graecorum.